Assessment of RUFORUM member universities in Kenya - Mose, Lawrence; Gao, Lang; Beintema, Nienke M. (Regional Universities Forum for Capacity Building in Agriculture, 2018)
Credible quantitative and qualitative information on existing capacities in agricultural higher education agencies in Africa are important for decisionmakers at national, regional, and international levels. Decisionmakers require data and indicators for strategic planning, policy formulation, setting priorities and benchmarks, measuring progress toward benchmarks, and identifying capacity gaps. Decisionmakers need a better understanding of the specifics of existing staffing and student capacities in the higher education sector, as well as in the wider agricultural innovation systems in Africa south of the Sahara. Access to such information will result in better policies addressing capacity issues in agricultural higher education, research, extension, and other areas. The existence of such information, however, remains extremely limited.